Francisella sp., an emerging pathogen of tilapia, Oreochromis niloticus (L.), in Costa Rica - Soto, E (2009)
Francisella sp. is an emergent bacterial pathogen that causes acute to chronic disease in warm and cold water cultured and wild fish species. During the past 3 years, the bacterium has been detected in tilapia, Oreochromis niloticus, cultured in Costa Rica. Infected fish presented non-specific clinical signs, such as erratic swimming, anorexia, anaemia, exophthalmia and high mortality. Upon macro scopic and microscopic examination, several internal organs (mainly spleen and kidney) were enlarged and contained white nodules. Histological examination revealed the presence of multifocal granulomatous lesions, with the presence of numerous small, pleo morphic, cocco-bacilli. The bacteria were isolated from infected tilapia on selective media and grown on several media with and without antibiotics. Specific PCR primers to the Francisella genus were used to confirm the preliminary diagnoses. In comparison with several bacterial 16S rRNA sequences, our iso late was found to share 99% identity with other Fransicella spp. isolated from fish, and more than 97% identity to the human pathogen Francisella tularensis. Koch s postulates were fulfilled after exper imental intraperitoneal and gill exposure challenges